Comparative analysis of particle image velocimetry and acoustic Doppler velocimetry in relation to a pool-type fishway flow. Issue 4 (4th July 2017) - Quaresma, Ana L.; Ferreira, Rui M.L.; Pinheiro, António N.
ABSTRACT: Particle image velocimetry (PIV) and acoustic Doppler velocimetry (ADV) were used in a pool-type fishway with bottom orifices to measure velocity at several locations in planes parallel to the bottom and to the sidewalls. Estimates of parameters that influence fishways efficiency, such as water velocity and turbulent kinetic energy (TKE), were compared. Differences in temporal and spatial resolutions of both techniques were assessed. In-plane mean velocity magnitude showed very good agreement between both instruments, with raw measurements presenting similar values of the square of the sample correlation coefficient ( R 2 ) and the refined index of agreement ( dr ) as post-processed ones. The in-plane TKE agreement between both instruments greatly improved with post-processing, with R 2 and dr ranging from 0.92 to 0.99, whereas raw values were lower (0.49–0.85). Nonetheless, further investigation is needed on the efficiency of the denoising method at points with sharp velocity gradients in the horizontal velocity components (perpendicular to ADV axis components).